THE QUALITY-OF-LIFE DEVELOPMENT MODEL FOR THE DEPENDENT ELDERLY AND FAMILIES THROUGH COMMUNITY PARTICIPATION IN BANGKHLA DISTRICT, CHACHOENGSAO PROVINCE, THAILAND (Journal of Pharmaceutical Negative Results, 2023)
This research was aimed at developing a model for developing quality-of-life of the dependent elderly and their families through community participation in Bangkhla district, Chachoengsao province, Thailand. Populations of this participatory action research covered the dependent elderly and their families, representatives of government sectors, local government authorities, and community leaders whose functions were relevant to quality-of-life improvement in this area. Sixty samples and key informants were selected through purposive sampling and snow-ball techniques. Data were collected by in-depth interviews, focus group discussions. The research findings revealed that the model for improving quality-of-life of the dependent elderly and families comprised groups of people and organizations involved with the dependent elderly and families must collaboration, the health promotion hospital in which there were accessible data system, work monitoring system, training care givers, health volunteers, care managers, effective screening the elderly eligible benefit, elderly caregiving volunteer with assessing and giving care for the dependent elderly and families. Tambon administrative organizations and municipalities was the system for assisting the dependent elderly according to principles and criteria enacted by the National Security Health Office. Neighbors help observe and give moral support and assist when needed. Temple was central for mental care of community residents. Monks would give spiritual support to the dependent elderly and families in the village. School was the educational center for people in community while teachers offered guidance for children to respect adults and the elderly in both at home and in community. People in community harmonized helped one another without conflict.